Statistics in psychology using R and SPSS - Rasch, Dieter; Kubinger, Klaus D., 1949-; Yanagida, Takuya (Chichester, West Sussex, UK : John Wiley & Sons, 2011)
Statistics in Psychology covers all statistical methods needed in education and research in psychology. This book looks at research questions when planning data sampling, that is to design the intended study and to calculate the sample sizes in advance. In other words, no analysis applies if the minimum size is not determined in order to fulfill certain precision requirements. The book looks at the process of empirical research into the following seven stages: Formulation of the problem, Stipulation of the precision requirements, Selecting the statistical model for the planning and analysis, The (optimal) design of the experiment or survey, Performing the experiment or the survey, Statistical analysis of the observed results, Interpretation of the results.
Concept of the book -- Measuring in psychology -- Psychology : an empirical science -- Definition : character, chance, experiment, and survey -- Numerical and graphical data analysis -- Probability and distribution -- Assumptions : random sampling and randomization -- One sample from one population -- Two samples from two populations -- Samples from more than two populations -- Regression and correlation -- One sample from one population -- Samples from more than one population -- Model generation -- Theory-generating procedures.
Includes bibliographical references and index.
Print version record.
Keywords: SPSS (Computer file); SPSS (Computer file); SPSS (Computer file); Psychometrics; Social sciences -- Statistical methods -- Computer programs; Psychometrics -- methods; Statistics as Topic -- methods; Software; PSYCHOLOGY -- Research & Methodology; Psychometrics; Social sciences -- Statistical methods -- Computer programs; Electronic books